Determinants of Adverse Perinatal Outcomes in Ibadan, Nigeria: The influence of maternal lifestyle. - Ikeola A Adeoye; Chioma O Unogu; Kofoworola Adediran; Babatunde M Gbadebo (PLOS Global Public Health)
Adverse perinatal outcomes (APO) are unfavourable incidents of at least one of the following: low birth weight, preterm delivery, stillbirths, neonatal deaths, and perinatal deaths. They contribute significantly to neonatal and infant morbidity and mortality, developmental abnormalities, and long-term impairments. Studies are lacking on the influence of maternal lifestyle on APO in Nigeria. Hence, we investigated the determinants of APO using the Ibadan Pregnancy Cohort Study (IbPCS) data and examined 1,339 mothers who had hospital delivery. The outcome variable was APO (low birth weight, birth asphyxia and preterm delivery). Explanatory variables comprised Antepartum Depression (Edinburgh Depression Scale ≥ 12), Physical activity (Pregnancy Physical Activity Questionnaire (PPAQ), Dietary pattern (Qualitative Food Frequency Questionnaire (FFQ), Maternal Stress (Perceived Stress Scale), Alcohol consumption, and Tobacco exposure. We used binary and multiple logistic regression to assess the associations between the risk factors and adverse perinatal outcomes at a significant P-value <0.05. Prevalence of APO was 26.7%, 95%CI (24.4-29.1); low birth weight - 8.5%, 95%CI (7.0-10.1) preterm delivery 14.8%, 95% CI (12.9-16.7); birth asphyxia 16.3%, 95%CI (14.0-18.9). The factors associated with LBW were being a female infant AOR: 2.00, 95%CI (1.13 -3.52); emergency caesarean section AOR: 2.40, 95%CI (1.06-5.42); a history of hypertension in pregnancy AOR: 3.34, 95%CI (1.45 -7.52). Preterm birth was associated with being poor AOR: 2.00, 95%CI (1.13 -3.52); history of stillbirth AOR: 2.05, 95%CI (1.14-3.68); antepartum depression AOR: 1.87, 95%CI (1.08-3.25). Of the lifestyle factors examined, only a high protein diet with a non-alcoholic beverage dietary pattern had a statistically significant association with preterm birth [AOR: 0.50, 95%CI (1.08-3.52)]. However, lifestyle factors had no significant association with LBW and birth asphyxia in our study. Understanding these risk factors can help policymakers and healthcare professionals create cost-effective interventions to curtail the burden of APO in Nigeria.